Implicit and explicit knowledge of inflectional morphology. (21st July 2015) - ROGERS, JOHN; RÉVÉSZ, ANDREA; REBUSCHAT, PATRICK
ABSTRACT: This study set out to test the degree to which second language inflectional morphology can be acquired as a result of incidental exposure and whether the resulting knowledge is implicit (unconscious) or explicit (conscious) in nature. Participants were exposed to an artificial language system based on Czech morphology under incidental learning conditions. In the testing phase, a grammaticality judgment test was utilized to assess learning. In addition, subjective measures of awareness and retrospective verbal reports were used to measure whether the acquired knowledge was conscious or not. The results of the experiment indicate that participants can rapidly develop knowledge of second language inflectional morphology under incidental learning conditions in the absence of verbalizable rule knowledge.